Striving for Justice in Tony Goldwyn's Conviction Movie (2010): An Individual Psychological Perspective - RAHMAWATI, NETTY NUR (2012)
This study is aimed to show the search for justice in Conviction Movie (2010) using individual psychological perspective. It is done by establishing two objectives; the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on individual psychological analysis. This research is descriptive qualitative research. The primary data taken from a movie entitled Conviction which was released in 2010 directed by Tony Goldwyn and the secondary data source, including the script of the movie and the other information taken from the book and website from internet that were relevant to the subject matter. The study comes to following conclusions. First based on the structural analysis, the director, Tony Goldwyn adapted and built his movie by employing the right mise-en-scene and proper cinematography so that the movie formed a good unity to deliver a moral message that justice is more important than individual happiness. Second, based on the individual psychological analysis, Goldwyn illustrates a psychological phenomenon in which the major character is obsessed with the freedom of her brother because she believes that her brother is innocent. It is apparent that in this movie, Goldwyn also criticizes how the police is sometimes arrogant and reckless in implementing law enforcement.